The use of a lacertid lizard as a model for reptile ecotoxicology studies: part 2 - biomarkers of exposure and toxicity among pesticide exposed lizards - Amaral, Maria José (2019)
As part of a wider study examining the impacts of corn pesticides on lacertid lizards in north-western Portugal, we examined various physiological, biochemical, and histological biomarkers of exposure and effect among field populations of Podarcis bocagei. Biomarkers included body condition index, standard metabolic rate, locomotor performance, parasitization, glutathione oxidative pathways and related enzyme activity, lipid peroxidation and liver and testis histology. Few of the various biomarkers investigated provided statistically significant evidence of toxic effect. However, using a weight of evidence approach, we conclude that pesticides are affecting lizards living in the vicinity of pesticide exposed corn agriculture sites. Lizards from these locations present a profile of animals under metabolic stress with reduced condition indices, increased standard metabolic rate, lower incidence of hepatocyte vacuolation, altered iron metabolism, increased activation of GSH oxidation pathways, and even increased prevalence of hemoparasites.